Respuesta :

frika

Answer:

See explanantion

Step-by-step explanation:

Consider the equation [tex]x^2-4x + 4 = 2x-1-x^2.[/tex] This equation consists of two parts:

  • left part is defined by the function [tex]y=x^2-4x+4;[/tex]
  • right part is defined by the function [tex]y=2x-1-x^2.[/tex]

Both these functions are quadratic and determine parabolas. The graph of the function

[tex]y=x^2-4x+4=(x-2)^2[/tex]

is parabola tangent to x-axis at point (2,0) with branches going up. The graph of the function

[tex]y=2x-1-x^2=-(x-1)^2[/tex]

is parabola tangent to x-axis at point (1,0) with branches going down (see diagram). As you can see from the diagram these two parabolas do not intersect, then there are no solutions.

Ver imagen frika

Answer:

The graph shows two parabolas having vertical flip with one another

Step-by-step explanation:

See the attached image

Ver imagen zainebamir540